The Work Motivation, Stress, and Environment Shaping Organizational Citizenship Behavior: Motivasi Kerja, Stres, dan Lingkungan Kerja Membentuk Organizational Citizenship Behavior - Errinda Ayu Dwi Pramesti; Lilik Indayani (Academia Open, 2023)
Background: Organizational Citizenship Behavior (OCB) is crucial for organizational effectiveness, driven by factors like work motivation, stress, and the work environment. Knowledge Gap: Limited studies examine the combined influence of these factors on OCB, particularly in production settings. Aims: This study investigates how work motivation, stress, and the work environment, both individually and collectively, affect OCB. Results: The findings indicate that all three factors significantly and positively impact OCB, both individually and together. Novelty: This research demonstrates the simultaneous influence of motivation, stress, and environment on OCB in a production context. Implications: Improving employee motivation, stress management, and fostering a positive work environment can effectively enhance OCB, supporting better organizational outcomes. Highlights: Work motivation, stress, and environment each significantly affect OCB. These factors combined have a stronger impact on OCB. Enhancing motivation, stress management, and work conditions can improve organizational performance. Keywords: Work Motivation, Work Stress, Work Environment, Organizational Citizenship Behavior, Employee Performance